IMPLICATIONS OF THE UKRAINE WAR FOR INDONESIAN MILITARY AND SECURITY COOPERATION: A POLICY ANALYSIS - Aris Sarjito (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
The ongoing Ukraine war has significant global geopolitical implications, reshaping security policies and international relations. For Indonesia, as a non-aligned and strategic player in Southeast Asia, understanding the impact of this conflict is crucial for adjusting its defense and security cooperation strategies. This research aims to analyze the implications of the Ukraine war on Indonesia's military and security cooperation policies. A qualitative approach was employed, using secondary data from government documents, policy analyses, and academic literature to explore Indonesia's diplomatic stance, defense collaborations, and alignment with major powers. The findings reveal that the Ukraine war has prompted Indonesia to reconsider its defense policies, particularly in diversifying military procurements, avoiding over-reliance on any specific nation, and enhancing regional security partnerships. Additionally, Indonesia's emphasis on non-alignment has been strengthened, with a focus on ensuring strategic autonomy amidst the growing tensions between global powers. The research concludes that the conflict has reinforced Indonesia's proactive engagement in regional security forums and prompted a recalibration of its defense procurement strategies. These insights contribute to understanding how global conflicts can influence the defense policies of non-aligned states like Indonesia.